HUBUNGANÂ KELEKATANÂ DENGANÂ KECERDASANÂ EMOSIÂ DANÂ PENYESUAIANÂ SOSIALPADAÂ ANAKÂ USIAÂ DINIÂ - henni anggraini; sarah emmanuel (Universitas Muhammadiyah Surabaya, 2016)
AttachmentÂ isÂ isÂ theÂ tendencyÂ andÂ desireÂ ofÂ anÂ individualÂ isÂ aÂ childÂ toÂ seekÂ proximity withÂ theirÂ guardiansÂ (MonkÂ etÂ all,Â 2004).ThereÂ areÂ fourÂ basicÂ principlesÂ ofÂ theÂ bond betweenÂ parentÂ andÂ childÂ isÂ the physicalÂ needsÂ ofÂ childrenÂ forÂ foodÂ andÂ warmthÂ thatÂ filled byÂ theirÂ mother,Â theÂ encouragementÂ ofÂ originÂ whichÂ isÂ ownedÂ byÂ theÂ childÂ toÂ clingÂ toÂ the mother'sÂ chest,Â theÂ babyÂ neededÂ toÂ touchÂ andÂ clungÂ byÂ aÂ person,Â andÂ theÂ disappointment ofÂ theÂ babyÂ asÂ itÂ isÂ expelledÂ fromÂ inÂ theÂ wombÂ (Bowlby,Â 1969).Â TheÂ qualityÂ ofÂ aÂ relationship betweenÂ aÂ childrenÂ andÂ aÂ parentsÂ areÂ anÂ importantÂ factorÂ forÂ developmentÂ ofÂ children. TheÂ theoryÂ ofÂ attachmentÂ explainedÂ thatÂ childrenÂ needÂ attachmentÂ withÂ atÂ leastÂ one caregiverÂ toÂ developÂ emotionalÂ andÂ socialÂ development.Â ThisÂ studyÂ aimsÂ toÂ determineÂ the relationship betweenÂ attachmentÂ ofÂ emotionalÂ intelligenceÂ andÂ socialÂ adjustmentÂ inÂ early childhood.Â ThisÂ studyÂ usedÂ quantitativeÂ methodsÂ toÂ theÂ subjectÂ 35Â studentsÂ ofÂ classÂ BÂ TK muslimatÂ NUÂ 22Â agedÂ 5â€7Â years.Â TheÂ collectingÂ ofÂ dataÂ obtainedÂ throughÂ aÂ scaleÂ of attachmentÂ betweenÂ aÂ childÂ andÂ aÂ parents,Â theÂ scaleÂ ofÂ emotionalÂ intelligenceÂ andÂ social adjustment.Â Furthermore,Â theÂ dataÂ wereÂ analyzedÂ byÂ usingÂ ProductÂ MomentÂ Pearson correlationÂ analysisÂ usingÂ SPSSÂ 21.0Â forÂ windows.Â TheÂ resultÂ showedÂ thatÂ thereÂ wasÂ a positiveÂ andÂ significantÂ relationshipÂ betweenÂ attachmentÂ withÂ emotionalÂ intelligenceÂ and socialÂ adjustmentÂ inÂ earlyÂ childhoodÂ (rxy1Â =Â 0,537;Â rxy2=Â 0,513;Â pÂ =Â 0,005Â <Â 0,05).